A REPRESENTATIVE OF HUMOUR PRESS IN THE SECOND CONSTITUTIONALIST PERIOD: FALAKA NEWSPAPER - Cihat TANIŞ (Fırat University, 2019)
The first official newspaper of Ottoman Empire, which was published in 1831, is Takvim-i Vekayi. Since a great deal of newspapers began during Reorganisation and First Constitutional Periods, the government desired to control the media by means of various laws and regulations. This condition continued until Second Constitutional Era. Thus, there were many important developments occurred in media likewise in other areas with the announcement of Second Constitution. Following the announcement day of Second Constitution, newspapers were published without censorship. It was also observed that especially the number of humour newspapers dramatically increased. Falaka is a humour newspaper that was pressed on Mondays and Thursdays. The publisher and the editor was Mahmut Nedim. It was published as 4 pages in Manzume-i Efkâr Press in Bâb-ı Âli Avenue. It was a typical member of humour press during Second Constitutional Period, which released 19 volumes in total. Falaka, which referred mainly political and social topics as press policy, preferred to emphasize particularly Italy-Turkish War and cholera outbreak. Additionally, articles in dialogue style were frequently taken in part.